Penerapan Hybrid Contract sebagai Inovasi pada Produk Pembiayaan Multijasa di Lembaga Keuangan Syariah - Hardiati, Neni; Prasetyo, Yoyok; Herdiana Abdurrahman, Nana (Transpublika Publisher, 2021)
Rapid product development is carried out by Islamic Financial Institutions (LKS) in providing alternative services to the needs of the community which are carried out based on sharia principles. The development of these services is provided both in the form of banks and non-banks as well as in the form of storage or other types of services as well as in the form of financing. However, due to more complex customer needs, LKS requires innovation in order to get convenience in its operational activities. So, in innovating with hybrid contracts, it becomes an important thing. This research uses a literature study with a normative juridical approach, which is carried out by collecting, studying and reviewing books, scientific magazines and documents related to this research such as theses and scientific articles. The results of the study state that in the application of hybrid contracts in multi-service financing products at Islamic Financial Institutions (LKS) generally use ijarah contracts according to the DSN-MUI fatwa. In this case, if the LKS uses the ijarah contract, it must comply with the provisions of the fatwa as the service provider or the benefits obtained from the LKS. Meanwhile, if in a hybrid contract one or more contracts are added, in this case it is added with a wakalah contract, then the customer has the power to carry out his own costs. However, if there are customers who still have to pay ujrah for the ijarah contract, it is called usury. Because this is not justified in sharia principles and is not in accordance with the ijarah fatwa concerning the multiservice, the bank does not fulfill its service obligations as the fatwa regarding multiservice as well as the kafalah contract. Thus, there is an alternative in this multi-service financing, namely by using hawalah bil ujrah and wakalah contracts which are more flexible and their implementation as an innovation, namely combining these contracts with the aim of making banking operations easier, reaching wider and able to meet the needs of more customers.